Fish diversity in relation to fish economics of Isapur dam, from Pusad, Yavatmal District (Maharashtra), India. - Pawar SK (International Journal of Life Sciences, 2017)
The Study fish diversity and analysis of fish Economics of Isapur dam from Pusad Dist. Yeotmal in Maharashtra region. The water body resource for human consumption, significant role in the human economy and agriculture. special reference to fish diversity and fish rare. The importance of fish economics in fish Production and Analysis in fish of data were also Studied.